Skrining Fitokomia Dan Uji Aktivitas Antibakteri Ekstrak etanol daun jeluak (Microcos tomentosa (L.)) Terhadap Bakteri Escherichia coli dan Staphyloccocus aureus - Toni Andareas Sitompul; Haris Munandar Nasution; Yayuk Putri Rahayu; Muhammad Amin Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Bacterial infections caused by Staphylococcus aureus and Escherichia coli remain major public health problems. Resistance to conventional antibiotics has driven the search for alternative antibacterial agents from natural sources. Jeluak leaves (Microcos tomentosa L.) have been traditionally used as an antimicrobial, yet scientific evidence regarding their antibacterial activity is limited. Objective: This study aimed to perform phytochemical screening and evaluate the antibacterial activity of the ethanolic extract of Jeluak leaves against E. coli and S. aureus. Methods: This was an experimental laboratory study. Extraction was carried out by maceration using 96% ethanol. Phytochemical screening included tests for alkaloids, flavonoids, tannins, saponins, steroids, and glycosides. Antibacterial activity was tested using the disc diffusion method on Mueller Hinton Agar at extract concentrations of 10%, 30%, 50%, and 70%. Chloramphenicol and DMSO were used as positive and negative controls, respectively. Inhibition zone diameters were measured after 24 hours of incubation at 37°C. Results: Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, steroids, and glycosides. The extract produced inhibition zones against E. coli of 6.3 mm, 9.3 mm, 12.2 mm, and 13.61 mm, and against S. aureus of 7.51 mm, 10.7 mm, 12.7 mm, and 14.28 mm, respectively. According to CLSI 2020 criteria, the 70% concentration was categorized as intermediate, while concentrations of 10–50% were resistant. The positive control was sensitive against both bacteria. Conclusion: The ethanolic extract of Jeluak leaves (Microcos tomentosa L.) possesses antibacterial activity against E. coli and S. aureus, with higher effectiveness against S. aureus than E. coli. Secondary metabolites such as flavonoids, tannins, and alkaloids are suggested to contribute to the antibacterial mechanism